A Study on Responsive Powder Concrete: A Ultra High Strength Concrete: Investigating the use of Reactive Powder Concrete in prefabricated constructions (Journal of Advances and Scholarly Researches in Allied Education, 2021)
High-strength, next-generation concrete, Reactive Powder Concrete (RPC) is made from aninnovative blend of powdered ingredients. Cement (often Portland cement), fine sand, silica fume, quartzpowder, and high tensile steel fibers make up the other components of reactive powder concrete. Veryhigh performance concrete includes reactive powder concrete. The use of steel pellets can increase thecompressive strength of this concrete from its already impressive 200 MPa to a maximum of 800 MPa.With a flexural strength between 25 and 40 MPa, this new kind of concrete has an enhanced ductilebehavior. The goal of this study is to determine whether or not prefabricated constructions, and inparticular angle sections, can benefit from using Reactive Powder Concrete. In order to have a handle onhow to proceed with this project, it is necessary to first define the properties of RPC blend.